Microplastics in fishes from an estuary (Minho River) ending into the NE Atlantic Ocean. (December 2021) - Guilhermino, Lúcia; Martins, Alexandra; Lopes, Clara; Raimundo, Joana; Vieira, Luis R.; Barboza, L. Gabriel A.; Costa, Joana; Antunes, Carlos; Caetano, Miguel; Vale, Carlos
Abstract: Wild fish ( Cyprinus carpio, Mugil cephalus, Platichthys flesus ) from an estuary of the NE Atlantic coast were investigated for plastic contamination ( N  = 128). From the 1289 particles recovered from fish samples, 883 were plastics. Among these, 84% were fibres and 97% were microplastics. Thirty-six polymers were identified. The number of microplastics (mean ± SD) per individual fish (MP/fish) was 8 ± 6 in C. carpio, 10 ± 9 in M. cephalus and 2 ± 2 in P. flesus . The means of MP/fish per body site were 6 ± 7 in gastrointestinal tract, 0.5 ± 1.1 in gills, 0.3 ± 0.7 in liver and 0.6 ± 1.2 in muscle samples. A few large fibres in liver (≤ 4841 μm) and muscle (≤ 5810 μm) samples were found. The results evidence the existence of high fish contamination by microplastics and reinforce the need of further research on plastic pollution in estuaries. Graphical abstract: Unlabelled Image Highlights: Fish (flounders, mullets, carps) were studied for plastic (PL) contamination. 883 PL were recovered, of which 97% were microplastics (MP). 94% of fish had PL with a mean of 8 ± 8 PL per fish. PL in the gastrointestinal tract, gills & muscle, and MP in the liver were found. Fibres had size ≤ 4841 μm in the liver, and ≤ 5810 μm in the dorsal muscle.